Effects of ferric derisomaltose on postoperative anaemia in adult spinal deformity surgery: a study protocol for a randomised controlled trial - Yuguang Huang; Jianxiong Shen; Yang Jiao; Jing Zhan; Weiyun Chen (BMJ Open)
Introduction Postoperative anaemia is prevalent in adult spinal deformity (ASD) surgery in association with unfavourable outcomes. Ferric derisomaltose, a novel iron supplement, offers a promising solution in rapidly treating postoperative anaemia. However, the clinical evidence of its effect on patients receiving spinal surgery remains inadequate. This randomised controlled trial aims to evaluate the safety and efficacy of ferric derisomaltose on postoperative anaemia in ASD patients.Methods and analysis This single-centre, phase 4, randomised controlled trial will be conducted at Department of Orthopaedics at Peking Union Medical College Hospital and aims to recruit adult patients who received ASD surgery with postoperative anaemia. Eligible participants will be randomly assigned to receive ferric derisomaltose infusion or oral ferrous succinate. The primary outcome is the change in haemoglobin concentrations from postoperative days 1–14. Secondary outcomes include changes in iron parameters, reticulocyte parameters, postoperative complications, allogeneic red blood cell infusion rates, length of hospital stay, functional assessment and quality-of-life evaluation.Ethics and dissemination This study has been approved by the Research Ethics Committee of Peking Union Medical College Hospital and registered at ClinicalTrials.gov. Informed consent will be obtained from all participants prior to enrolment and the study will be conducted in accordance with the principles of the Declaration of Helsinki. The results of this study are expected to be disseminated through peer-reviewed journals and academic conferences.Trial registration number NCT05714007.